Pelatihan Pembuatan Media Pembelajaran Interaktif di Era Kurikulum Merdeka Bagi Guru SMPN 31 Padang - Rahmi, Rahmi; Hamdunah, Hamdunah; Fitri, Dewi Yuliana (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
One way to improve the quality of education in the 5.0 era and in accordance with the demands of the current Indonesian curriculum is merdeka curriculum. Teachers are required to have professional competencies, including the ability to innovate in learning media and develop them. The development of learning media in the form of interactive learning media is very important in order to increase interest in learning, the learning process and learning outcomes and not deviate from the competencies to be achieved. The development of today's increasingly sophisticated technology has resulted in a change in the paradigm of teaching and learning methods, teachers as educators are required to be able to develop all potential. Teachers are asked to continue to innovate in developing AI-based interactive learning media to help the learning process to be effective and interesting that is in accordance with the characteristics of students at school. The results of observations at SMP Negeri 31 Padang, the use of interactive learning media is still lacking. Teachers do not have experience and special competencies in developing innovative learning media. Therefore, training was held on making Interactive Learning Media in the Merdeka Curriculum Era Using Canva AI for Teachers of SMP Negeri 31 Padang. The implementation of this community service has had a positive impact on improving teacher skills in developing learning videos and is an important step in adapting technology. The use of technology makes learning more dynamic and effective, creating a learning environment that allows for deeper exploration, interaction and understanding for students.